The scope of the concept of information and the future of information science - Stodola, Jiří Tomáš (Array, 2019)
The key concept of information science is the concept of information which is tied to a number of complications. The main problem is that there is no definition of this concept. The purpose of this article is an analysis of the concept of information from the position of classical logic. The main method of the article is a conceptual analysis. First, we briefly deal with the overview of the concepts of information, with concepts and their definition as such and with the scope of the concept of information. Then, we provide an analysis of 31 important definitions of the concept of information which were developed within the scope of information science and related fields, and we consider relations between the concept of information and the concepts in other disciplines. Conceptual analysis of the concept of information leads to the conclusion that information is probably a concept that somehow addresses the entire reality, thus that it is a term, which is in the classical logic described as transcendental. This fact, in the view of the fact that information science is a special field, seems to be a serious methodological problem. Problems associated with the broadness of the concept of information have three possible solutions: transformation of information science into the universal science, narrowing the concept of information to a special term, or replacement of the concept of information by a different one. At the end of the article, we briefly point out our solution to the problem.